Integral methods in science and engineering computational and analytic aspects - Constanda, C. (Christian); Harris, P. J. (Paul John) 1964- (Birkhäuser Boston, 2011)
The system study of the physical world is largely based on the design of mathematical models using many different types of ordinary differential, partial differential, integral, and integro-differential equations. The solutions of these equations are therefore of great interest to practitioners and to science in general. With a wealth of cutting-edge research in the field, Integral Methods in Science and Engineering: Computational and Analytic Aspects provides a vivid picture of both the development of theoretical integral techniques and their use in specific science and engineering problems. The volume is an outgrowth of talks presented by world-renowned researchers at the Eleventh International Conference on Integral Methods in Science and Engineering held in Brighton, UK, July 12?14, 2010. The array of topics they address is immense, ranging from theoretical advances in boundary integral methods to applications of analytic and numerical quadrature techniques as diverse as integral equations, finite and boundary elements, conservation laws, hybrid approaches, and more. With ample coverage of theory and applications, this book will be a valuable resource for researchers in applied mathematics, physics, and mechanical and electrical engineering, for graduate students in these disciplines, and for various other professionals who use integration as an essential technique in their work.